Designing a Model for the Implementation and Deployment of Quality 4.0 Using an Integrated Approach: Delphi Technique and Structural Equation Modeling in a Research Industrial Organization - Abbasi, Morteza; Bakhoda, Ali; Norozi, Mojtaba (International journal of industrial engineering and operational research, 2024)
The aim of this research is to create a framework for assessing the factors that contribute to successful implementation of Quality 4.0 in research industries. Initially, ten drivers were identified through a literature review. Then, significant indicators were determined using expert opinions and the Delphi technique. To evaluate the model's fit and the impact of each component, structural equation modeling(SEM) and associated tools, including measurement model fit, structural model fit, and overall model fit, were used. A 34-question questionnaire on a five-point Likert scale was designed for this purpose. The study included 155 managers and employees from research industries, with a sample size of 110 individuals determined using Cochran's formula and distributed through convenience sampling. Qualitative findings led to the identification of 12 main components, which were refined to reach expert consensus using a three-stage Delphi technique. The results from the fitted structural model revealed the high impact of the following components in order: financial resources, leadership, technological infrastructure, big data control, organizational agility, employee cooperation, rewards, organizational culture, management systems focused on program development, training, vision, and employee competence and skills. This research addresses the knowledge gap in the implementation of Quality 4.0 within research industries.